Revitalization of the Concept of Educational Axiology: Perspectives of Islamic Philosophy - Malik, Muh Syauqi; Maslahah, Maslahah (Belajea: Jurnal Pendidikan Islam, 2021)
The axiology of primary Islamic education is a discourse that is still very meaningful and relevant today. All Islamic education processes, whether in linking curricula, educators, educational staff, students, institutions, and so on, have one typical estuary, namely supporting axiology in primary Islamic education. This exposure is needed to explain the axiology of education from various points of view, the axiology in Islam, the urgency and function of axiology of primary Islamic teaching, the branch of axiology called ethics and aesthetics, and the essence of axiology in Islamic primary education. The author uses qualitative research methods literature review to summarize, analyze, and synthesize various references to complete writing. The research results reveal that Islamic primary education’s axiology talks about the value or benefits of Islamic education at the primary level. The concept of axiology in Islam is taken from the word qoyyimah, which means straight, straight in the interpretation of the path leading to God, a straight forward way with the provisions of the Qur’an and Hadith. The urgency of primary Islamic education’s axiology to straighten the education system elements to stay on the right path. The axiology function of primary Islamic education includes speculative, normative, criticism, and theory. Ethics is the study of values and moral and aesthetic attitudes, which is part of the philosophy of values and evaluation that views human work from a beautiful and unfavorable perspective. The essence of axiology in primary Islamic education is to form human beings in the human person.